The Effect of Eating Speed at Breakfast on Appetite Hormone Responses and Daily Food Consumption. Issue 1 (1st January 2015) - Shah, Meena; Crisp, Kelli; Adams-Huet, Beverley; Dart, Lyn; Bouza, Brooke; Franklin, Brian; Phillips, Melody
Abstract : Background: The effect of eating speed at a meal on appetite gut hormone responses and future food consumption is not clear. This study examined the effect of eating speed at breakfast on postprandial gut hormone responses, subjective appetite, and daily food consumption. Methods: Twenty-five participants [68% men; age, 25.9 (8.1) years; body mass index, 25.0 (3.2) kg/m 2 ] were recruited. Each participant consumed the same breakfast at a slow (30 minutes) and fast (10 minutes) speed, on 2 separate days, in a randomized crossover design. Blood samples were collected in the fasting state and 3 hours postprandially during each eating condition. Appetite was assessed over the same period using visual analog scales. Blood concentrations of orexigenic hormone, ghrelin, and anorexigenic hormones, glucagon-like peptide-1 (GLP-1) and peptide YY (PYY), were determined. Daily food intake was measured, by food recall, after the slow and fast breakfast. Results: Mixed-model repeated-measures analysis showed no eating condition or eating condition by time interaction effect on ghrelin, GLP-1, PYY, hunger, or fullness. Significant eating speed by time interaction effect on desire to eat was found ( P = 0.007). Desire to eat was lower at 60 minutes ( P = 0.007) after breakfast began during the slow versus fast eating condition. Eating speed at breakfast did not affect daily energy and macronutrient intake. Conclusions: Eating speed at breakfast did not affect postprandial ghrelin, GLP-1, PYY, hunger, and fullness values or daily energy and macronutrient intake. Desire to eat was lower at 60 minutes in the slow versus fast eating condition, but this result could not be explained by the changes in meal-related hormones measured in the study.